Why South Africa's energy-poverty policy ignores female well-being : a case of non-decision-making? - Fuma, Ayanda (Energy Research Centre, 2016)
In South African urban-informal contexts characterized by high levels of unemployment, women still have a close relation to the household. Females shoulder most of the burden associated with fulfilling domestic energy requirements. Despite this, energy-poverty policies like the Free Basic Alternative Energy Policy of 2007 ignore the specific challenges faced by women such as the financial implications of procuring daily domestic energy. This study adds insight to this issue by adopting two approaches: firstly, this study explores views captured in twenty semi-structured interviews from a sample of 12 females and 8 males living in an informal settlement, located north of Durbanville in the Western Cape Province. This thesis relies on a case study design based on this informal settlement to describe the nuances and gender specific experiences which exist in managing domestic energy. Secondly, an unobtrusive research approach is taken, relying on an analysis of secondary data from online media and academic platforms. The data is analysed using Bachrach and Baratz (1962) guide to uncover power dynamics veiled in the formal processes of energy-poverty policy development in South Africa. This thesis asks how energy-poverty policy can contribute to addressing the so-called gender-energy-poverty nexus, recognising that social constructs of gender and policy formulation processes may be under-pinned by dynamics of non-decision-making. The main findings of the study show that attributes of non-decision-making which feature in both the formal and informal power dynamics perpetuate female hardships in energy management. Social norms (informal power dynamics) influence the division of household labour including domestic energy management, which renders energy a major pre-occupation for women particularly. Furthermore, not recognizing informality in energy-poverty policy (formal power dynamics) negatively impacts women's well-being as women are dissatisfied with poor performing cooking and lighting fuels which negatively impacts young children's health, including inadequate options for food storage due to limited appliance use in the un-electrified informal settlement. Recommendations for the Free Basic Alternative Energy Policy to address energy-poverty in a gender-sensitive way may help to alleviate the negative impacts of securing daily energy on female informal settlement dwellers.